Sourgrass phenological stage and efficacy of ACCase-inhibiting herbicides - C. Presoto,Jéssica (2020)
Abstract Background: Sourgrass (Digitaria insularis) is a highly disseminated weed in Brazil. It is a perennial grass weed that has high infesting capacity in agricultural areas and presents glyphosate-resistant biotypes. An effective post-emergence control of sourgrass plants depends on their phenological stage at the time of herbicide application. Objective: This work was developed with the objective of evaluating the effect of the sourgrass phenological stage at the time of herbicide application on the efficacy of ACCase-inhibiting herbicides. Methods: Two independent experiments were conducted under greenhouse conditions to evaluate two ACCase-inhibiting herbicides: clethodim, and haloxyfop. The treatments were applied using a completely randomized block design, with an 8×4 factorial arrangement consisted of 8 herbicide rates (4, 2, 1, 1/2, 1/4, 1/8, and 1/16 times the recommended rate, and a control plot without herbicide application) and four phenological stages of sourgrass. Results: The development of sourgrass plants after tillering decreased the efficacy of the herbicide molecules; however, clethodim and haloxyfop were efficient to control sourgrass at earlier developmental stages. Morphological, anatomical, and physiological changes in older plants may explain the lower susceptibility to herbicides. Conclusions: Other control techniques should be considered for sourgrass plants at later developmental stages, such as sequential application or herbicide mixtures, to increase the efficacy of ACCase herbicides.